2023
DOI: 10.1590/1984-0462/2023/41/2021145
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of metabolic syndrome and its components in Brazilian adolescents: a systematic review and meta-analysis

Abstract: Objective: To determine the prevalence of metabolic syndrome (MS) and its components among Brazilian adolescents. Data source: Databases, such as LILACS, MEDLINE, and SciELO, were searched for original cross-sectional studies published between 2010 and 2021. The inclusion criteria were determined based on the mnemonic CoCoPop — Condition, Context, and Population: studies determining the prevalence of MS and its components (condition) in the general population of Brazilian adolescents, female and male (populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 38 publications
1
7
0
1
Order By: Relevance
“…Our findings show that the main risk factors related to MS in farmers are gender, age, BMI and land ownership and that the main attributes for the high prevalence of MS are obesity, the substitution of in natura foods for ultra-processed foods and the inflammatory profile. The findings of this study corroborate the results of the literature by noting that women, the elderly and the obese are more likely to have MS [3,6,7,9,16]. We also considered laboratory data for a more robust analysis of this condition and found that HDL, blood pressure and WC are the most prevalent components of MS, with a higher BP in men and high WC and lower HDL in women.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our findings show that the main risk factors related to MS in farmers are gender, age, BMI and land ownership and that the main attributes for the high prevalence of MS are obesity, the substitution of in natura foods for ultra-processed foods and the inflammatory profile. The findings of this study corroborate the results of the literature by noting that women, the elderly and the obese are more likely to have MS [3,6,7,9,16]. We also considered laboratory data for a more robust analysis of this condition and found that HDL, blood pressure and WC are the most prevalent components of MS, with a higher BP in men and high WC and lower HDL in women.…”
Section: Discussionsupporting
confidence: 88%
“…In the systematic review covering countries such as Colombia, Peru, Mexico, Brazil, Venezuela and others, the most frequent components of MS were low HDL-c (62.9%) and abdominal obesity (45.8%) [33]. In addition to these studies conducted in America, surveys conducted in other regions also show similar results [9,17,34].…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Sixteen studies assessed the prevalence of obesity, which ranged from 5.4% (Ethiopia) to 49.4% (China). 3,5,18,21,25,36,39,43,46,49,54,63,64,67,74,88 Seven studies (n = 340 240) were included in the quantitative synthesis, 3,25,36,39,43,49,54 providing data on pooled prevalence of children obesity (13.9% [95% CI 8.8%-19.9%]), adult obesity (26.1% [95% CI 7.9%-50.1%]), and overall obesity (17.3% [95% CI 6.1%-32.6%]) (Figure 2). Heterogeneity between studies was considerable (I 2 = 100.0%).…”
Section: Obesitymentioning
confidence: 99%
“…Because many people "lose" their MetS, the clinical significance of the condition in childhood and adolescence is still unknown. However, central obesity, which increases the risk of developing the condition at one age (Paiva et al, 2022), is a risk factor for the condition at 9 to 10 years of age. A deeper comprehension of the prevalence of the MetS and its underlying mechanism is necessary.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%